Second bogolyubov theorem for systems of difference equations - Danilov, V. Ya.; Martynyuk, D. I.; Pan'kov, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish an analog of the second Bogolyubov theorem for a system of difference equations.